2013
DOI: 10.1038/npp.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Deprivation Influences P300 Markers of Cognitive Control

Abstract: Studies suggest that reduced cognitive control due to nicotine withdrawal may have a critical role in promoting tobacco use. The P3 family of event-related brain potential (ERP) components is thought to serve as markers of cognitive control processes. Unfortunately, existing research that examines the effects of nicotine deprivation on P3 amplitude has been marred by small sample sizes and other design limitations. The present study sought to determine the effects of nicotine deprivation on P3b and P3a amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 33 publications
4
49
1
Order By: Relevance
“…Despite an extensive literature on smoking withdrawal (Ashare, Falcone, & Lerman, 2013;Baker et al, 2012;Bidwell et al, 2013;Etter, Ussher, & Hughes, 2012;Evans et al, 2013;Hendricks & Leventhal, 2013), few studies have evaluated early withdrawal effects-those that emerge during the first minutes and hours after the last cigarette. To the best of our knowledge, only two studies have systematically evaluated the early time course of smoking withdrawal effects (Brown et al, 2013;Hendricks, Ditre, Drobes, & Brandon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite an extensive literature on smoking withdrawal (Ashare, Falcone, & Lerman, 2013;Baker et al, 2012;Bidwell et al, 2013;Etter, Ussher, & Hughes, 2012;Evans et al, 2013;Hendricks & Leventhal, 2013), few studies have evaluated early withdrawal effects-those that emerge during the first minutes and hours after the last cigarette. To the best of our knowledge, only two studies have systematically evaluated the early time course of smoking withdrawal effects (Brown et al, 2013;Hendricks, Ditre, Drobes, & Brandon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the P3b is enhanced following nicotine and tobacco use. 23,24 Although the P3b was not significantly influenced by product type, this may reflect the relatively smaller sample size of the present investigation. Previous work has also generally demonstrated modulation of the N2 in response to nicotine and tobacco use, although the results have been mixed (for a review see: Pritchard et al 22 ).…”
Section: Discussionmentioning
confidence: 65%
“…This is consistent with literature indicating that the ability of tobacco products to improve executive functioning is driven by nicotine, as compared to placebo. 18,23,42,43 This literature would suggest that the smokeless tobacco product that causes the greatest influence on executive function does so as the result of its nicotine content alone. However, it is also known that factors other than nicotine can influence the response to a product [44][45][46] and not all studies of nicotine have found evidence for nicotine alone influencing executive function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations